Neurofeedback for moral enhancement: irreversibility, freedom, and advantages over drugs - Savulescu, J; Maslen, H (Taylor and Francis (Routledge), 2016)
Akabayashi and colleagues examine the potential therapeutic applications of decoded neurofeedback in treating psychiatric conditions such as depression, and developmental disorders. We challenge the authors’ claim that the irreversibility of the effects of neurofeedback necessarily presents a problem for its use for moral enhancement.